Re-imagining suburbia: the case of Lynwood, Menlo park and Hezelwood in Pretoria - Gildenhuys, Johannes S (My University, 2018)
With the current rapid rate of urbanisation, declining inner cities spaces and urban sprawl, questions are being asked about the sustainability of our urban areas. The issue of sustainability and sustainable development has been the central focus of the development debate since the late 1980s but have been a major theme for the past 150 years when the first questions about creating more sustainable, compact cities surfaced. Even in South Africa, there is concern about the inefficient spatial structure of our cities. However, South Africa has a complicated past, and our lack of urban sustainability is seen as a result of modernist and apartheid type planning. After the fall of apartheid many new policies and legislation has been enacted to transform South Africa’s towns and cities to more compact, integrated and sustainable urban environments. What is apparent is that despite these new policies, the country has failed to achieve these spatial ideals. These policies and legislation has focused much of its attention on the regeneration of inner city areas and the outlying sprawling suburbs caused by outmigration and rapid urbanisation. The focus on these areas has meant that other spaces in the city have been neglected. A new opportunity presents itself in what is termed the older inner ring suburbs. These include those suburban areas that were developed during the great suburban boom of the 1930s to the 1950s and that have mostly been forgotten in the urban imagination. Many authors see these spaces as the solution to our urban futures. These overlooked environments hold “tremendous potential for achieving promise for achieving smart growth goals in suburbia in that it is dense, typically located near commercial and retail centers, and houses a population that has shown a propensity for non-auto travel” (Larco, 2009: 167). This provides the opportunity to improve densities within these suburban spaces and give effect to concepts such as smart growth and new urbanism. This new focus on suburban redevelopment, and specifically on older suburbs with untapped potential for creating denser sustainable urban environments need guidance in order to achieve sustainability. Many authors have long argued that urban design provides the required guidance to reach our urban sustainability ideals. These authors all focus on urban design as a catalyst and facilitator to achieve humane urbanity and is therefore seen as the key enabling tool for the modification and improvement of settlements. The research report is therefore concerned with how densification can exploit the potential of often forgotten inner ring suburban areas to improve the overall sustainability and inefficient urban form of our cities. The adjacent suburbs of Lynnwood, Menlo Park and Hazelwood in Pretoria were chosen as the specific area for investigation for this thesis. As older, established suburbs, with pressure for redevelopment and new development, it possesses the desirable attributes with the possibility of being integrated back into the urban fabric and to form a successful multi-use hub of activity.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of Master of Urban Design Johannesburg 2017